2014
DOI: 10.5604/12321966.1129950
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback training for peak performance

Abstract: Neurofeedback training in the subject under study increased the amplitude of the monitoring component of ERPs generated in the anterior cingulate cortex, accompanied by an increase in beta activity over the medial prefrontal cortex. Taking these changes together, it can be concluded that that even a few sessions of neurofeedback in a high performance brain can significantly activate the prefrontal cortical areas associated with increasing confidence in sport performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Which is exactly what was observed in the ERP difference waves induced by the treatment of the presented patient! These results mean that the symptoms of post-surgical depression might be treated with the use of the proposed methodology [17]. As proved in another study by the authors [18,19,20], as in this case, the patient was able to returned to work with an improved quality of life.…”
Section: Discussionsupporting
confidence: 56%
“…Which is exactly what was observed in the ERP difference waves induced by the treatment of the presented patient! These results mean that the symptoms of post-surgical depression might be treated with the use of the proposed methodology [17]. As proved in another study by the authors [18,19,20], as in this case, the patient was able to returned to work with an improved quality of life.…”
Section: Discussionsupporting
confidence: 56%
“…This approach would be an effective tool for player selection and could lead to more successful matches (Rampinini et al 2009). Additionally, these results also support EEG neurofeedback as a potential diagnostic tool for use as a treatment protocol for chronic fatigue syndrome (CFS) symptoms (James and Folen 2010;Pachalska et al 2017) and to create the possibility of peak performances (Graczyk et al 2014).…”
Section: Discussionmentioning
confidence: 63%
“…The results of this study show that correct feedback by neurofeedback lead to improve archers performance while incorrect feedback lead to reducing their performance. In another case study by Graczyk et al (2014) on the Olympic athletes after injury results indicate increase athletic performance after neurofeedback training. Also, Shaw et al, (2012) showed increased balance and performance of gymnasts in the competition after neurofeedback training.…”
Section: Discussionmentioning
confidence: 96%